Testing the CAPM-GARCH Models in the GCC-Wide Equity Sectors - BENDOB, Ali; CHIKHI, Mohamed; BENNACEUR, Fatma (Asian Journal of Economic Modelling, 2017)
This paper tests the conditional and non-conditional versions of the Capital Asset Pricing Model (CAPM) in Gulf Cooperation Council GCC capital markets -wide equity sectors upon daily data during the period from February 22ed 2007 to February 22ed 2012. In the empirical analysis, we used Generalized Autoregressive Conditional heteroscedasticity (GARCH) models with CAPM. Main findings seem to show that the CAPM-EGARCH (1.1) appears more advantages than the traditional CAPM at the sectors considered in this study. This approach can be improved and developed in order to be widely applied as this model takes into account shocks, especially in the crisis period where volatilities are very high.